Hands-on chatbot development with Alexa skills and Amazon Lex : create custom conversational and voice interfaces for your Amazon Echo devices and web platforms.: create custom conversational and voice interfaces for your Amazon Echo devices and web platforms. (2018) - Unknown
No abstract available